19 Engaging children and young people on medications administration using augmented reality interactive narratives. (15th December 2021) - Zheng, Lixia; Visram, Sheena; Hall, Angela; Sridharan, Shankar; Taylor, Andrew; Sebire, Neil J; Rogers, Yvonne
Abstract : Introduction: Augmented Reality (AR) overlays context-sensitive information onto the real world in a meaningful way. As AR bridges the gap between the real and virtual world, it holds potential to enhance the learning experience of users. This is because AR can offer contextually enriched interactions with content to illustrate complex concepts more intuitively and provide unique discovery paths for individual exploration. Diseases like Cystic Fibrosis (CF) require strict compliance to pancreatic enzyme replacement therapy (PERT), which plays an important role in the body's digestive process. This requires patients to be aware of their condition and to participate in their care. For cases such as these, one possibility is a medication bottle with interactive AR attributes serving as a supplementary way of providing patients with essential medical guidance/education. Method: A co-design process with Specialist Dietitians (x3) used sketches, storyboards, personas, paper prototypes and a digital prototype to develop and deliver the concept of an interactive medication label for PERT education. Results: A proof of concept smartphone AR application for children with CF was designed to supplement current guidance for PERT. Based on the results of user research, 7 key design decisions to meet primary user needs were evolved during the process, leading the final design to a cartoon-style, marker-based AR application with a narrative structure, consisting of four main parts triggering by various markers: (i) an introduction to the digestive process, (ii) Mechanisms of PERT action (iii) instructions for taking PERT and (iv) extra precautions like dose and allergy. Conclusion: Early evaluation with clinicians showed that interactive narrative holds potential for delivering educational content to patients about their medications and care. Future research will involve patient advisory groups to explore whether these types of technologies can help to reduce anxiety, medication errors, and offer engaging experiences of care through interactive experiences